The Piermont allochthon revisited and redefined at its type locality - Timms, Nicholas Eric (Geological Society of America, 2004)
Regional lithostratigraphic and structural mapping of the Piermont allochthon of northwestern New England at its type locality indicates that the Foster Hill fault, the supposed sole thrust, is a stratigraphic boundary. Rather, the allochthon lies above the Bean Brook fault, covers a much smaller area than suggested previously, and is limited to the vicinity of Piermont, western New Hampshire. The allochthon, which primarily consists of rocks correlated with the Silurian age Rangeley Formation of Maine, has horizons of metamorphosed polymictic conglomerate at its base. Rocks directly below theallochthon are correlated with the metasedimentary, Ordovician-aged Albee Formationand contain abundant metamorphosed dykes and sills that do not cross the sole detachmentof the allochthon. Analysis of macro- and mesoscale structures indicates local reservation of fold hinges and overprinting foliations oblique to and later than those previously described and has allowed the deformation history to be signifi cantly extended by several events. Emplacement of the allochthon early in the deformation history at metamorphic conditions caused NW-SE elongation lineations of clasts in conglomerate at the base of the allochthon. The relict foliations and fold hinges are commonly preserved below the allochthon, suggesting that these rocks have had a more protracted deformation history relative to rocks in the allochthon. The new interpretation of the Piermont area provides a framework to build a more thorough tectonic history for this part of the New England Appalachians.